Non-recommended routes of application in ozone therapy, a critical review (Ozone Therapy Global Journal, 2018)
Ozone used within the determined therapeutic windows is absolutely safe and more effective than golden standard medications in numerous pathologies. However, there are practitioners who for the interest of increasing cost effectiveness and increasing speed in treatments, pretend to cure chronic diseases applying alternative administration ways, using high ozone doses, which are neither standardized, nor supported by pre-clinical / clinical data, nor evaluated toxicologically. In this review an analysis of the bibliographical data concerning efficacy and safety of this methods was analyzed. The search included a review of scientific articles and experimental results papers in the MEDLINE and Zotero ISCO3 Ozone Database, between the years 1980-2018. Descriptors: ozone therapy, toxicology, side effects were used. The primary (original articles) sources of information were located. The most representative emerging therapies: direct intra venous application (DIV), Robins method of direct intravenous ozone therapy℠ (RMDIV ℠), Hyperbaric (HBO3) multi passes method, high dose ozone therapy (HDO), and Intraperitoneal Ozone (IPO3) are lack of clinical evidences and represent a serious risk for the human health. A rational clinical protocol fits to the good clinical practice and supported by and ethic committee is needed to prof it efficacy prior to be introduced in clinical practice. The emergent are not recommend for its clinical application (except patients enrolled in a clinical trial) until new scientific evidence of the benefit/risk ratio is provided..